(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2023)
Background: Ageing is an emerging issue for global public health including Bangladesh which is underwent a demographic transition and experiencing an increasing proportion of the elderly population. We conducted this study to document the characteristics of the patients admitted into a newly established geriatric centre in a tertiary-level hospital in Bangladesh. Materials and methods: We conducted this descriptive cross-sectional study among 194 older adults admitted into the geriatric centre of Chittagong Medical College Hospital of Bangladesh. A structured questionnaire was utilized to collect the information. The study participants’ Socio-Economic (SE) class was determined by modified Kuppuswamy’s classification. The data were analyzed with Stata SE 17.0 for descriptive and inferential statistics. Results: Among the 194 participants, 66.5% represented the middle SE class while about one-fourth were from the Upper SE class. Gender (p-value: 0.029) education (pvalue: <0.0001), smoking (p-value: 0.034) and BMI (pvalue: 0.040) were found to be associated with the SE class. The common presenting complaints were respiratory distress, cough, lethargy, constipation, vomiting, anorexia, chest pain and insomnia, while the predominant clinical signs were tachypnoea, cardiological abnormalities, anaemia and fever. Conclusion: More extensive research is needed for the increasing population of the elderly in Bangladesh to understand the epidemiology and determinants of different co-morbidities. JCMCTA 2023 ; 34 (1) : 3-9